1990
DOI: 10.1288/00005537-199004000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term endotracheal intubation on vocal function

Abstract: Transient voice change associated with endotracheal intubation has generally been attributed to vocal fold trauma. To assess the role of altered vocal fold function in transient voice change, a study was designed to evaluate the audioacoustic, endoscopic, and laryngostroboscopic characteristics of the postintubation voice. Vocal function of 10 patients undergoing short-term outpatient surgical procedures using general anesthesia and endotracheal intubation were studied preoperatively and postoperatively. A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2007
2007
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
2
28
0
3
Order By: Relevance
“…Administration of anesthetic agents may affect the vocal tract neuromuscular activity, fine motor control, and sensorium, all of which can result in changes in the fundamental frequency and perturbation parameters. 9,26 The significant decrease in the MPT witnessed in our study can be secondary to the postanesthetic decrease in the breathing support discussed previously, to a decrease in the breathing control secondary to the aforementioned changes in the vocal folds, or to the surgical impact on the power source for phonation, such as the chest and abdomen.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Administration of anesthetic agents may affect the vocal tract neuromuscular activity, fine motor control, and sensorium, all of which can result in changes in the fundamental frequency and perturbation parameters. 9,26 The significant decrease in the MPT witnessed in our study can be secondary to the postanesthetic decrease in the breathing support discussed previously, to a decrease in the breathing control secondary to the aforementioned changes in the vocal folds, or to the surgical impact on the power source for phonation, such as the chest and abdomen.…”
Section: Discussionmentioning
confidence: 59%
“…Both laryngeal and extralaryngeal structures may be affected. 9 At the glottic level, damage to the mucosal surface of the vocal folds can markedly change the voice. Desiccation of the mucosal surface secondary to inhalation of gaseous anesthetic substances or intake of drying medications such as atropine, which was consistently given preoperatively to all our patients, can result in an increase in the vocal fold viscosity and impaired vibration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their analysis, singing skills of a patient had no impact on the development of these laryngopharyngeal symptoms. Acoustic studies [14][15][16][17] have shown that jitter (fluctuation in vocal pitch) and shimmer (fluctuation in vocal intensity) have consistently increased after extubation, while maximum phonation time (ability to sustain a prolonged vowel sound) is decreased, thus underscoring the temporary instability of the voice after extubation.…”
Section: Postoperativementioning
confidence: 99%